SIFAT-SIFAT LAPISAN KULIT LUAR BINTANG NEUTRON - Purwati, Fera Gustina; Sulaksono, Anto (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2014)
The main contributions for determining the equation of state of the outer crust of neutron star are from nuclear, electronic, and lattice. We have already studied a toy model developing first time by Roca-Maza that use two assumptions i.e, nucleus are liquid drop (LDM) and electrons are relativistic Fermi gas. For knowing the variations of elements in the outer crust, the parameters of the model are obtained by fitting to atomic nuclear mass tables by Audi Wapstra 2003. To show the accuracy of toy model’s calculation, we compare it with the result of the neutron drip in this region. This result calculation of toy model successfully showing the neutron drip on the value MeV and that corresponding to the element. Keywords: outer crust, neutron star, neutron drip, LDM.